A Laboratory Investigation of Spume Generation in High Winds for Fresh and Seawater. Issue 21 (14th November 2019) - Mehta, S.; Ortiz‐Suslow, D. G.; Smith, A. W.; Haus, B. K.
Abstract: Given spume's role in mediating air‐sea exchange at the base of tropical cyclones or other storm events, the focus of studies on spray dynamics has been within the marine environment. In contrast, spume production in nonseawater bodies has been underexplored and potential differences between sea and freshwater are neglected. The laboratory remains the primary means for directly observing spray processes near the surface because of the challenges to making robust field measurements. There is no standardization on the water type used for these experiments, and the effect this has on the generation process is unknown. This adds uncertainty in our ability to make physically realistic spume generation functions that are ultimately applied to the geophysical domain. We have conducted a laboratory experiment that aims to address this simple, yet overlooked, question of whether water type impacts the spume droplet concentration entrained in the air flow above actively breaking waves. We compared directly imaged concentrations for fresh and seawater droplets produced in 10‐m equivalent winds from 36–54 m/s. Substantially higher concentrations of seawater spume were observed, as compared to freshwater across all particle sizes and wind speeds. The seawater particles' vertical distribution was concentrated near the surface, whereas the freshwater droplets were more uniformly distributed. Our statistical analysis of these findings suggests significant differences in the size‐ and height‐dependent distributions response to increased wind forcing between fresh and seawater. These unexpected findings suggest an unanticipated role of the source water physiochemical properties on the spume generation mechanism. Key Points: The first laboratory study comparing spume generation in freshwater and real seawater under hurricane‐force wind speeds has been conducted Across all particle sizes and wind speeds tested, significantly more seawater spume was produced than in freshwater conditions As compared to freshwater, the distribution of seawater spume particles in the air was significantly more concentrated near the water surface